Trends in Flipped Classroom of Higher Education: Bibliometric Analysis (2012–2022) - Fika Rakhmalinda (Journal of Research in Mathematics, Science, and Technology Education, 2024)
The “flipped classroom” learning model in higher education that requires preparation of technological and pedagogical knowledge in Higher Education. This study was viewed bibliometrically from 2012-2022 using data collection techniques microsoft excel and Vos Viewer. The purpose of this study is to explain the flipped classroom trend in high education. This document is taken from the collection of Scopus articles. The keyword used was “flipped classroom” with a total of 2821 documents, but 2054 were selected for bibliometric analysis with certain criteria. The results showed that the United States of America was the document publication with the highest number of citations. This study presents data from Scopus as many as 2054 published data. In 2015 the article belongs to O’Flaherty J., Phillips achieved the most citations, namely 1011 other authors. While in 2017-2021 the number of citations is as much as19902 and is expected to continue to increase in 2022 (currently n=121 Scopus documents, citations of 289 articles). Another finding is that the trend of flipped classrooms continues to increase in Higher Education to hone 21st century skills.